Bioactive Potential of Salicornia europaea Extracts Antioxidant, Anti-Inflammatory, Antivenom, and Anticancer Assay on HepG2 Apoptosis Induction - Manoranjitham, Malaichamy; Hemalatha, Thangam; Vijayalakshmi, Annamalai (Asian Journal of Biological and Life Sciences, 2025)
Background: As an ethnomedical herb, Salicornia europaea is widely used in India to cure a variety of illnesses. Objectives: The present studies evaluated an aqueous extract of Salicornia europaea for its anti-inflammatory, antioxidant, anticancer, apoptotic, and anti-venom qualities. Materials and Methods: The DPPH photometric assay, OH radical scavenging capacity, anti-inflammatory activity, Cyclooxygenase (COX), Lipoxygenase (LOX), anticancer, apoptotic, and anti-venom action are a few examples of in vitro models that were used to measure antioxidant activity. Results: The study supported the traditional use of the aforementioned plants in inflammatory disorders by finding that the antioxidant and anti-inflammatory effects of plant extracts may be due to the inhibition of DPPH and OH, COX, and LOX enzymes, respectively. Salicornia europaea's aqueous extract was extremely selective (p<0.005) against HepG2 cells, generating morphological changes, according to the MTT experiment. Conclusion: Because of its strong PLA2 inhibition, the aqueous extract of Salicornia europaea was found to have the strongest and safest anti-inflammatory, antioxidant, anticancer, and anti-venom properties based on the available data.
Keywords: Cyclooxygenase; DPPH; Hydroxyl; Inflammation; lipoxygenase; Salicornia europaea